2004
DOI: 10.1385/mo:21:1:81
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Kinetics of Donor Lymphoid Cells in Response to G-CSF Administration May Affect the Incidence and Severity of Acute GvHD in Respective HLA-Identical Sibling Recipients

Abstract: Granulocyte-colony stimulating factor (G-CSF), in addition to myeloid and stem cells, mobilizes a large number of lymphoid cells. We examined which lymphoid populations were mobilized in 21 consecutive donors of peripheral blood stem cells (PBSC) and whether the differences in mobilization could affect the incidence of acute and chronic GvHD in respective HLA-identical recipients. G-CSF administration induced significant increases of donor B (CD3-CD19+) lymphocytes and slight increases of T (CD3+) and cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…20,22,23 There are contradictory reports on changes in the absolute numbers of NK cells and their proportion within total lymphocytes, following rhG-CSF administration. 20,22,23,[29][30][31][32][33] Functional assays produced equally contradictory results, 31,[33][34][35][36][37][38] although in most instances impaired natural cytotoxic activity against NK-sensitive cell lines was evidenced after rhG-CSF treatment. Two studies reported a decreased expression of proinflammatory cytokines such as IFN-g, IL-2 and TNF-a 31,39 after rhG-CSF mobilization; interestingly, they observed no change in perforin, Fas and Fasligand expression on allogeneic NK cells, a result consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,22,23 There are contradictory reports on changes in the absolute numbers of NK cells and their proportion within total lymphocytes, following rhG-CSF administration. 20,22,23,[29][30][31][32][33] Functional assays produced equally contradictory results, 31,[33][34][35][36][37][38] although in most instances impaired natural cytotoxic activity against NK-sensitive cell lines was evidenced after rhG-CSF treatment. Two studies reported a decreased expression of proinflammatory cytokines such as IFN-g, IL-2 and TNF-a 31,39 after rhG-CSF mobilization; interestingly, they observed no change in perforin, Fas and Fasligand expression on allogeneic NK cells, a result consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups 17,33,35,39 already demonstrated that rhG-CSF administration in vivo had no effect on the expression of CD2, CD7, CD8, CD16, CD25, CD94, CD161 and NKB1 receptors on PB NK cells. There is only one report that suggest a downmodulation of CD56 cell surface density, on both CD56 bright /CD3 À cells and CD56 dim / CD3 À cells.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of developing GvHD following haematopoetic stem cell transplantation (HSCT) is associated with low numbers of Tregs in the periphery,100 and in vivo expansion of Tregs post-HSCT using low-dose IL-2 has demonstrated efficacy against GvHD 101 102. Studies in mice involving infusion of cultured CD4 + CD25 + T cells resulted in a significantly reduced GvHD phenotype,103 and in humans it was found that infusion of freshly isolated donor Tregs given at the same time as haplotype mismatched HSCT prevented the development of GvHD 104…”
Section: Treg Therapy In Other Conditionsmentioning
confidence: 99%
“…For example, the induction of NK cell effector function in response to the c-Kit tyrosine kinase inhibitor Gleevec (STI571) in patients with gastrointestinal stromal tumors, or in response to exosomes in patients with melanoma, correlated with decreased T reg cell numbers, increased antitumoral responses, and delayed cancer progression (Ghiringhelli et al, 2005, 2006). In patients undergoing HLA-identical blood stem cell transplantation, increased donor T reg cell numbers were associated with reduced NK cell cytotoxic activity (Trzonkowski et al, 2004b). Acute depletion of T reg cells in mice also lead to a significant increase in NK cell numbers, in line with the phenotype of Foxp3-deficient Scurfy mice, which harbor abnormally activated and proliferating NK cells (Ghiringhelli et al, 2005; Kim et al, 2007).…”
Section: Nk Cell–t Reg Cell Cross-talkmentioning
confidence: 99%